KERAGAMAN FENETIK JENIS LAMUN DI PERAIRAN PANTAI DESA POKA BERDASARKAN MORFOMETRIK SERTA IMPLIKASINYA BAGI PEMBELAJARAN BIOLOGI - Tuapattinaya, Prelly Marsell J; Melay, Stevin; Siahaya, Calvin (Program Studi Pendidikan Biologi FKIP Unpatti, 2024)
Abstrak Background : This study aims to determine the phenetic diversity of seagrass species in the coastal waters of Waai Village based on morphometrics and their implications for biology learning. Methods : This research is a descriptive type of research, in which morphometric measurements are carried out to determine the phenetic diversity of seagrass species. sedan Results: The results of this study found four types of seagrass, namely Thalasssia hemprichii, Enhalus acoroides, Halophila pinifolia and Halophila ovalis. this indicates that the beach of Poka Village has a high phenetic diversity of seagrass species with varying morphometrics for each character and species, which is influenced by the type of substrate and environmental parameters. Seagrasses that have close kinship relations, namely, Thalasssia hemprichii and Enhalus acoroides are in one monophyletic group (ingroup) and have very close kinship. Likewise with and Halodule pinifolia and Halophila ovalis. The results of this study are implied in the form of teaching materials in the form of booklets that can be used by students as learning media.